Effectiveness Use Ice Breaking in Increase Participation Study Students on Learning Economics at State Senior High School 1 Tambang - Na’imah Na’imah; Hendripides Hendripides; Gani Haryana (Jaanur Elbarik Indonesia, 2026)
This research is motivated by the low participation of students in Economics subjects at SMA Negeri 1 Tambang. The purpose of this study was to determine the level of student participation before and after the application of ice breaking and to measure its effectiveness. The research method used is a Pre-Experimental Design with a One Group Pretest-Posttest Design. The research sample consisted of 29 students of class X Unggul 3 selected through purposive sampling. Data collection was carried out through observation and questionnaires. Data analysis was performed using descriptive statistics, normality tests, and hypothesis testing through Paired Sample t-Test and N-Gain Score analysis. The results showed an increase in the mean score of student participation from 47.17 (pre-test) to 66.10 (post-test). The N-Gain score obtained was 81.32%, which is in the